Dualitas PPPSRS pada Apartemen MP: Kesalahan Gubernur DKI Jakarta serta Solusinya - Faustine, Stefanie (Magister Kenotariatan Universitas Surabaya, 2024)
Abstract Each apartment has parts that are owned individually and parts that are owned jointly with the owner and/or other residents. The complexity of apartment ownership led to the creation of PPPSRS in Law 20/2011 to manage the shared ownership section. However, in several apartments, PPPSRS which should be responsible for regulating flat ownership, is involved in internal disputes to win positions. Like what happened at the MP Apartments, where there was a group of people who wanted to overthrow the previous PPPPSRS, thereby creating a duality of PPPSRS because the PPPSRS management had been approved by the Governor of DKI Jakarta. The purpose of this writing is to find out the causes of PPPSRS duality in MP Apartments and what the solution is. The research method in this writing is normative juridical methodology, using 2 (two) approaches, namely the statutory and conceptual approaches to identify and analyze relevant legal frameworks. The research results show that the duality of PPPSRS at MP Apartments occurred because the Governor of DKI Jakarta was not careful in ratifying PPPSRS at MP Apartments. In issuing the decision letter, the Governor of DKI Jakarta has violated the procedural and substantive elements based on article 52 of Law 30/2014. The solution to this problem is, based on article 33 of Law 20/2014, the regional government must issue a decision to withdraw the approval of PPPSRS in MP Apartments in accordance with the principle of contrarius actus so that there is no duality of PPPSRS in MP Apartments.